Recruiting for Epigenetic Research: Facilitating the Informed Consent Process. (6th June 2013) - Jallo, Nancy; Lyon, Debra E.; Kinser, Patricia Anne; Kelly, Debra Lynch; Menzies, Victoria; Jackson-Cook, Colleen
Abstract : Because the effects of epigenetic (gene-environment interaction) changes have been associated with numerous adverse health states, the study of epigenetic measures provides exciting research opportunities for biobehavioral scientists. However, recruitment for studies focusing on any aspect of genetics poses challenges. Multiple factors, including lack of knowledge regarding a research study, have been identified as barriers to recruitment. Strengthening the informed consent process through extended discussion has been found to be effective in recruiting for research studies in general, yet there is a paucity of information that focused on such a recruitment strategy for epigenetic studies. In this paper, we share our experiences with strategies to strengthen the informed consent process as well as provide samples of materials developed to heighten potential participants' understanding of epigenetics, in 4 epigenetic research studies with women from diverse backgrounds experiencing a range of health issues. The combined enrollment success rate for epigenetic studies using the process was 89% with participants representing a diverse population. We posit that carefully developed recruitment scripts provided a foundation for improving potential participants' understanding of the research project. Easy to understand illustrations of the epigenetic process provided a basis for active engagement and encouraged individual questions.